Diffusion law of coal gangue slurry and the application of fluidized filling technology of gangue in caving area - Ji-qiang Zhang; Xiang He; Ke Yang; Zhen Wei; Xin-Yuan Zhao; Jue-jing Fang (Scientific Reports, 2023)
Abstract In order to deeply study the basic characteristics, diffusion laws, and flow laws of coal gangue and coal gangue slurry, the basic characteristic parameters of coal gangue and coal gangue slurry were obtained through particle size distribution test, electron microscope scanning test, X-ray diffraction test, X-ray fluorescence spectrum test, and angle of repose test. The conveying performance test of coal gangue slurry was carried out, and based on this, a simulation test of coal gangue slurry caving areas was designed. The diffusion and flow laws of coal gangue slurry under the same inclination angle were summarized, and the field test of fluidization filling in the caving areas was conducted. The results show that: (1) The water-to-gangue ratio was the main controlling factor for the conveying performance of coal gangue slurry. The extensibility, slump, and bleeding rate of the coal gangue slurry increased with the increase of the water-to-gangue ratio. (2) The diffusion profile of coal gangue slurry at different dip angles was arc-shaped, and the diffusion distance of slurry increased with the increase of infiltration time. However, there were differences in the sustained diffusion ability of different dip angles. (3) At the same time interval, the spatial accumulation patterns of scattered gangue in different regions will lead to differences in the diffusion speed of the slurry. (4) Both burying and hanging pipes in the falling area can safely and efficiently fill the gangue slurry. The diffusion distance of the caving areas in the test working face was basically consistent with the diffusion distance of the slurry in the simulation test of the coal gangue slurry caving areas.